A prototype computer supported information relation analysis tool (COMSIRA) - Hashemipour, Majid; Deniz, Derviş Z.; Topuz, Cem; Anla?an, Ömer (American Society of Mechanical Engineers (ASME), 1997)
A methodology is proposed which aims at covering informational and functional analysis besides decision making processes. It comprises of a set of well defined steps and novel tools. The proposed methodology makes extensive use of reference architectures available. The methodology aims at using limited expertise, limited staff, and expenditure as it is especially suited for introducing CIM in SME's. A Computer Supported Information Requirement Analysis tool (COMSIRA) has been developed for the methodology, in order to capture and represent the approach of experienced analysts studying the enterprise-wide prospective CIM information requirements. This paper emphasizes the operational aspects of COMSIRA along with introducing the methodology. Some examples extracted from a real case implementation are also presented. © 1997 by ASME.
ASME 1997 Design Engineering Technical Conferences, DETC 1997 -- 1997-09-14 through 1997-09-17 -- Sacramento -- 167364
Keywords: Information management; Decision making process; Information relations; Information requirement; Information requirement analysis; Operational aspects; Real case; Reference architecture; Decision making